(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2023)
Sexual abuse of young children is a form of crime that is very destructive, both physically and psychologically. In the context of criminal law, existing regulations are often questioned for their effectiveness in providing justice for victims. Theoretically, the concept of legal protection for children, especially in cases of sexual abuse, has been regulated in various national and international legal instruments. However, there is still a gap between the written law and its implementation in the field, especially in dealing with cases of sexual abuse against early childhood. The main problem discussed in this article is how criminal law is able to provide justice for victims of early childhood sexual abuse. The article also examines the challenges in the law enforcement process and the obstacles faced, including social stigma and lack of access to rehabilitation services for victims. The novelty of this research lies in the critical analysis of current criminal law mechanisms, along with proposed legal reforms to strengthen child protection. The main focus of the research is to assess the effectiveness of the criminal law in accommodating the needs of victims of early sexual abuse, especially in the context of post-traumatic rehabilitation and recovery. The purpose of this study is to explore the extent to which the criminal law in Indonesia has succeeded in providing justice for victims of early sexual abuse and to identify factors that hinder the effective implementation of the law. The research methodology used a qualitative approach with a case study method. Data was collected through in-depth interviews with legal practitioners, child protection activists, as well as a review of relevant legal documents. The research also analyzed several cases of early childhood sexual abuse to assess the application of criminal law at the practical level. The results show that although the criminal law in Indonesia has provided a basis for legal protection for children, implementation in the field still faces various obstacles, including weak coordination between law enforcers, lack of sensitivity to victims, and lack of rehabilitation efforts that focus on victim recovery. The implications of this research are expected to serve as a basis for policy makers to formulate concrete steps to improve the criminal justice system, including by increasing the role of rehabilitation services and providing specialized training for law enforcement officials in handling cases of sexual abuse against young children